2018
DOI: 10.15517/iv.v19i33.32919
|View full text |Cite
|
Sign up to set email alerts
|

Señalización y seguridad vial en buses de tránsito rápido: el transmilenio en Bogotá

Abstract: El incremento de la accidentalidad vial en la mayoría de los países del mundo ha encendido las alarmas de la práctica de la movilidad urbana e interurbana contemporáneas. Los percances, ocurren tanto en sistemas de transporte público, como en vehículos privados o sistemas masivos de transporte. En el presente escrito, se estudia la influencia de la señalización en la seguridad vial de los usuarios del sistema Transmilenio en el eje troncal de la avenida Caracas en Bogotá, Colombia, a través del análisis descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In view of this situation, authors such as Y. Asprilla et al [5] have involved the concept of sustainable mobility through mass transportation where the use of motorcycles and vehicles with few passengers is minimized, and therefore, high road traffic is minimized leading to the reduction of AT. Likewise, as pointed out by the same author, but by means of [38], The inclusion of mass public transportation systems guarantees not only a safer transportation, but also a more complete one, according to the complementarity and organization of schedules established for the common transportation of citizens.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In view of this situation, authors such as Y. Asprilla et al [5] have involved the concept of sustainable mobility through mass transportation where the use of motorcycles and vehicles with few passengers is minimized, and therefore, high road traffic is minimized leading to the reduction of AT. Likewise, as pointed out by the same author, but by means of [38], The inclusion of mass public transportation systems guarantees not only a safer transportation, but also a more complete one, according to the complementarity and organization of schedules established for the common transportation of citizens.…”
Section: Resultsmentioning
confidence: 95%
“…It was found that motorcyclists are the most vulnerable road actors in the city for the time range studied, highlighting also that, until now, as transportation, this means of transport has been a tool for informal work as a growing phenomenon. As pointed out by Y. Lara et al [39], motorized urban mobility has always been the most vulnerable, where the implementation of AT mitigation policies will be essential.…”
Section: Discussionmentioning
confidence: 99%